The Medieval mystical tradition in England : Exeter Symposium VII : papers read at Charney Manor, July 2004 - Jones, E. A. (Edward Alexander), 1968- (D.S. Brewer, 2004)
The latest volume of proceedings in the series initiated by Marion Glasscoe in 1980 shares with its predecessors a concentrated focus on the English mystical authors and the reception of their continental contemporaries in medieval England. At the same time, it bears witness to the range of disciplinary approaches - literary, historical, theological, art historical - which are currently bearing fruit in research on the medieval mystical tradition.